Product Relatedness and Firm Exports in China - Poncet, Sandra; Starosta de Waldemar, Felipe (World Bank, Washington, DC, 2014)
This paper proposes the first evaluation using micro-level data of the gains from the consistency of activities with a local comparative advantage. Using firm-level data from Chinese customs over the 2000-6 period, the study investigates the relationship between the export performance of firms and how their products relate to local comparative advantage. The key indicator measures the density of the links between a product and the local product space. Hence, it combines information on the intrinsic relatedness of a good with information on the local pattern of specialization. The results indicate that exports grow faster for goods that have denser links with those currently produced in the firm's locality. The density of links between products seems to yield export-enhancing spillovers. However, this positive effect of product relatedness on export performance is mainly limited to ordinary trade activities and domestic firms. It is also stronger for more productive firms, suggesting that spillover diffusion may be hindered by insufficient absorptive capacity.